Investigation Of Receptivity Principles In The Entrances Of Cities (Case Study Of Ardabil Entrance From Heyran Road) - Vahidi, Taher; Faroughi, Seyed Mohammadreza; Sadughi, Aref (The Turkish Online Journal of Design Art and Communication, 2016)
Nowadays, urban growth has been so fast that proper urban standards are largely neglected. These standards include particular attention to the quality of the city's entrances and exits. Entrance spaces of cities connect the exterior domain of cites to the artificial atmosphere inside them. Uncontrolled urban development and inattention to appropriate spatial development patterns have led to weaknesses in the form and content of urban spaces. The present study is an attempt to investigate and analyze the entrance of Ardabil from the Heyran road. This is a descriptive analytical study and the data has been collected through library studies, Internet searches and field observations. In this article, above from analyzing the above-mentioned entrance, some suggestions have been presented to eliminate its disadvantages. The research results indicate that urbanism principles are not met in this entrance and that this entrance has some problems in terms of receptivity.
Keywords: city; entrance to the city; receptivity; Ardabil; şehir; şehir girişinde alıcılığı; Erdebil